Multidimensional Decomposition and Ensemble Modeling of Histatin 1 and Its Siblings : Detailing Structure and Biological Function Using an Integrative Approach - Svensson, Oskar; Gerelli, Yuri; Skepö, Marie ; 0000-0002-8639-9993 (Journal of Chemical Information and Modeling, 2025)
Histatins are a family of multifunctional, cationic histidine-rich saliva peptides. The most prominently represented are Histatin 1, Histatin 3, and Histatin 5. Despite considerable similarities in primary structure, the three members are known to display varied antimicrobial properties and healing abilities. This study aims to provide a detailed structural comparison of Histatin 1, Histatin 3, and Histatin 5, as well as a thorough investigation into the variation caused to the conformational ensemble of Histatin 1 upon phosphorylation. The study applies molecular dynamics simulation, small-angle X-ray scattering, circular dichroism, bioinformatics tools, and neutron reflectometry. A multidimensional decomposition technique and its connection to clustering methods are also presented. It was observed that the phosphorylation of Histatin 1 profoundly shifts the conformational ensemble and may act as a molecular switch that facilitates tooth enamel binding. Observations are provided on the killing mechanisms of Histatins concerning self-association and membrane rupturing.